The self-assembled nanoparticle-based multi-epitope influenza mRNA vaccine elicits protective immunity against H1N1 and B influenza viruses in mice - Di, Yaxin; Zhang, Chenchao; Ren, Zilin; Jiang, Renyue; Tang, Jiafeng; Yang, Songhui; Wang, Ziliang; Yu, Tong; Zhang, Tong; Yu, Ziping; Xu, Zhiqiang; Zhuang, Xinyu; et al. (Frontiers in Immunology, 2024)
The influenza virus is recognized as the primary cause of human respiratory diseases, with the current influenza vaccine primarily offering strainspecific immunity and limited protection against drifting strains. Considering this, the development of a broad-spectrum influenza vaccine capable of inducing effective immunity is considered the future direction in combating influenza.The present study proposes a novel mRNA-based multi-epitope influenza vaccine, which combines three conserved antigens derived from the influenza A virus.The antigens consist of M2 ion channel's extracellular domain (M2e), the conserved epitope of located in HA2 of hemagglutinin (H1, H3, B), and HA1 of hemagglutinin.At the same time, trimeric sequences and ferritin were conjugated separately to investigate the immune effects of antigen multivalent presentation.Results: Immunization studies conducted on C57BL/6 mice with these vaccines revealed that they can elicit both humoral immunity and CD4 + and CD8 + T cell responses, which collectively contribute to enhancing cross-protective effects. The virus challenge results showed that vaccinated groups had significantly reduced lung damage, lower viral loads in the lungs, nasal turbinates, and trachea, as well as decreased levels of pro-inflammatory cytokines.These findings clearly demonstrate the wide range of protective effects provided by these vaccines against H1N1 and B influenza viruses. The present finding highlights the potential of mRNA-based influenza vaccines encoding conserved proteins as a promising strategy for eliciting broad-spectrum protective humoral and cellular immunity against H1N1 and B influenza viruses.